Pengembangan Sistem Informasi Manajemen Membership Gym Terintegrasi Kartu Digital Menggunakan Metode Research and Development - Brian Fajar Adiyatma; Rauhulloh Ayatulloh Khomeini Noor Bintang (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Data management at Hercules Fitness Karanganyar, which still relies on manual methods using ledgers, serves as the primary background for this research. The problems encountered include the complexity of tracking active membership status, a high potential for duplicated payment records, and the time-consuming preparation of monthly reports, all of which decrease operational productivity. Therefore, this study aims to design and develop a web-based membership information system featuring a novel automated digital card integration and unified notification system utilizing the Laravel framework.This system is expected to facilitate member data administration, transaction recording, attendance tracking, training scheduling, notification delivery, and the provision of digital membership cards. The Research and Development (RnD) approach utilizing the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model was applied in this study, encompassing the phases of needs analysis, system architecture design, development, and evaluation. System testing was conducted at Hercules Fitness Karanganyar, involving 27 participants consisting of gym management and members. Data were collected through direct observation, interviews, and questionnaires. The results indicate that the developed application successfully streamlines the registration process, membership management, transaction tracking, and information delivery to members in a more systematic manner. Based on the Black Box testing, all crucial features on both the administrator and user interfaces operated validly according to the planned scenarios. Furthermore, the User Acceptance Testing (UAT) yielded a feasibility percentage of 88.49%, which based on Likert scale interpretation criteria classifying the system as highly feasible. In conclusion, this Laravel-based membership management software significantly enhances operational efficiency by automating daily administrative workflows and reducing data recapitulation time at Hercules Fitness Karanganyar. This research delivers a valuable practical contribution by providing a digital governance ecosystem blueprint that can be readily adopted by local sports service MSMEs to improve their service efficacy.